Orientacje zawodowe młodzieży akademickiej będącej w okresie tranzycji z edukacji na rynek pracy - Kanclerz, Bożena (Wydawnictwo Naukowe UAM, 2016)
The modern world, which is characterized by diversity, uncertainty and ambiguity, affects the functioning of the younger generation. Young people experience a variety of problems associated with entering into adulthood. Being on the stage “between” youth and adulthood requires countless choices. The functioning of youth is still an interesting cognitive topic, worthy of scientific knowledge, therefore, the article seeks to answer the question: What is the professional orientation of contemporary university students? The article thesis consists of two parts. The first part has a theoretical character. It deals with issues of professional orientation. The second part of the article is an empirical analysis and attempt to answer the research question: What are the professional orientations of students?
Professional Orientation of University Students in a Transition Period from Education to the Labor Market
Keywords: university students; professional orientation of young people; work; career